Cross-border cooperation areas in north Bavaria and west Bohemia: Analysis and evaluation - Nicolai Teufel; Jörg Maier; Martin Doevenspeck (Cross-border spatial development in Bavaria: Dynamics in cooperation - Potentials of integration, 2022)
The EUREGIO EGRENSIS cooperation area was established in 1990 and is acknowledged and appreciated by political actors. It serves here as a heuristic for a multitude of spatial processes. On the one hand, it reflects the changing political and economic conditions of cross-border cooperation between Bavaria and the Czech Republic on a line of contact between two peripheral regions remote from political and economic centres. On the other hand, a spatial analysis of the EUREGIO EGRENSIS and, in particular, discussion of its spatial delimitations and alternative spatial configurations provide insights into debates surrounding the increasing macro-regionalisation and metropolisation of cross-border cooperation. In this article, the authors analyse modes of cooperation in the north Bavarian and west Bohemian border area. The EUREGIO EGRENSIS is often referred to as the most important institution of crossborder cooperation for the border region due to the long-standing trust between the actors involved. However, there is a certain reluctance among political actors in Bavaria and the Czech Republic to discuss the spatial, thematic or institutional expansion of cross-border cooperation. Based on the positive evaluation of the EUREGIO EGRENSIS cooperation area and trends towards larger cooperation regions, the idea of a meso area in the central European zone was discussed with stakeholders in the border area - roughly the area between the cities of Nuremberg, Erfurt, Chemnitz and Plzeén. Despite socioeconomic similarities and manifold functional interdependencies, this idea was met with scepticism.
urn:nbn:de:0156-41580587; hdl:10419/253270; https://econpapers.repec.org/RePEc:zbw:arlabe:34
Keywords: 710; European integration; cross-border cooperation; spatial planning; Bavaria; Czech Republic